Infrared spectroscopy of solid normal hydrogen doped with CH3F and O2 at 4.2 K: CH3F:O2 complex and CH3F migration - Abouaf-Marguin, L.; Vasserot, A.-M. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
Double doping of solid normal hydrogen with CH3F and O2 at about 4.2 K gives evidence of (ortho-H2)n:CH3F clusters and of O2:CH3F complex formation. A FTIR analysis of the time evolution of the spectra, in the ν3 C–F stretching mode region, points out a behavior of the clusters very different from that of (ortho-H2)n:H2O clusters. The main point is the observation of CH3F molecules migration in solid para-H2 at 4.2 K, which is a behavior different from H2O in identical experimental conditions. This is proved by the increase with time of the CH3F:O2 complex integrated intensity with a rate constant K = 2.7(2) ∙10–4 s–1.